Toward a research agenda on climate‐related migration. (7th April 2020) - Andrews, Clinton J.
Abstract: Climate change is one of the many stressors to which humans must adapt. Environmental concerns usually combine with other factors such as poverty, ethnic strife, or poor governance to become serious enough problems to warrant strong action. Migration away from affected areas is one time‐tested response. This article proposes a migration‐oriented research agenda for industrial ecology based on an examination of migration flows and ways of thinking about them, variations across contexts, implications for infrastructure and housing, the framing of climate‐related migration, and short‐term and longer‐term fluctuations in the demand for shelter and services in high and low income countries. Elements of this agenda include understanding decentralized migration decisions, developing socio‐ecologically based solutions for migration‐related problems, and embracing an urban focus that makes infrastructures more adaptable and makes cities more resilient and equitable.